Hierarchically targetable polysaccharide-coated solid lipid nanoparticles as an oral chemo/thermotherapy delivery system for local treatment of colon cancer. (March 2019) - Shen, Ming-Yin; Liu, Te-I; Yu, Ting-Wei; Kv, Reesha; Chiang, Wen-Hsuan; Tsai, Yuan-Chung; Chen, Hsin-Hung; Lin, Sung-Chyr; Chiu, Hsin-Cheng
Abstract: Although oral formulations of anticancer chemotherapies are clinically available, the therapeutic action relies mostly on drug absorption, being inevitably accompanied with systemic side effects. It is thus desirable to develop oral therapy systems for the local treatment of colon cancers featured with highly selective delivery to cancer cells and minimized systemic drug absorption. The present study demonstrates the effective accumulation and cell uptake of the doxorubicin and superparamagnetic iron oxide nanoparticles-loaded solid lipid nanoparticle (SLN) delivery system for chemo/magnetothermal combination therapy at tumors by hierarchical targeting of folate (FA) and dextran coated on SLN surfaces in a sequential layer-by-layer manner. Both the in vitro and in vivo characterizations strongly confirmed that the dextran shells on SLN surfaces not only retarded the cellular transport of the FA-coated SLNs by the proton-coupled FA transporter on brush border membranes in small intestine, but also enhanced the particle residence in colon by specific association with dextranase. The enzymatic degradation and removal of dextran coating led to the exposure of the FA residues, thereby further facilitating the cellular-level targeting and uptake of the SLNs by the receptor-mediated endocytosis. The evaluation of the in vivo antitumor efficacy of the hierarchically targetable SLN therapy system by oral administration showed the effective inhibition of primary colon tumors and peritoneal metastasis in terms of the ascites volume and tumor nodule number and size, along with the absence of systemic side effects. Graphical abstract: Image 1